Satisfaction of Healthcare Professionals and People With Diabetes With an Insulin Bolus Calculator Mobile Application. (July 2021) - Katz, Laurence B.; Hurrell, Graham; Venugopal, Usha; Cameron, Hilary; Shearer, David M.
People with diabetes (PWD) who need to take mealtime insulin to help control their blood sugar often have difficulty correctly calculating their dose due to consideration of many factors such as current blood glucose, carbohydrate consumption, active insulin duration, insulin-to-carb ratio, and insulin sensitivity. The Insulin Mentor, a bolus calculator tool in the OneTouch Reveal diabetes management app, uses an algorithm to automate many of these calculations and contains a link to a food diary to help estimate carbohydrate intake. In the current study, healthcare professionals and PWD from United States and Germany responded favorably to simulations of this calculator tool and compared it positively with other apps on the market. The Insulin Mentor may simplify the difficult process of correctly calculating mealtime insulin doses for PWD.